Analysis of microRNA Expression in Liquid-Based Cytology Samples May Be Useful for Primary Lung Cancer Diagnosis. Issue 4 (26th March 2021) - Araki, Yusuke; Arihiro, Koji; Yamaguchi, Kakuhiro; Sakamoto, Shinjiro; Horimasu, Yasushi; Masuda, Takeshi; Miyamoto, Shintaro; Nakashima, Taku; Iwamoto, Hiroshi; Fujitaka, Kazunori; Hamada, Hironobu; Hattori, Noboru
Abstract: Objectives: Bronchoscopy is frequently performed for patients suspected of having lung cancer; however, we sometimes fail to make a definitive diagnosis, resulting in additional invasive testing. Many studies indicate that microRNAs (miRs) are abnormally expressed in cancers. We examined the diagnostic value of 4 miRs (miR-21, miR-31, miR-182, and miR-183) extracted from liquid-based cytology (LBC) samples and validated whether they were diagnostically useful. Methods: We collected 18 surgically resected tissue samples and 136 LBC specimens obtained during bronchoscopic examination at Hiroshima University Hospital. We extracted RNA from these samples and compared the expression of 4 miRs by reverse transcription–quantitative polymerase chain reaction. Results: We confirmed that expression of the 4 miRs was significantly higher in cancer tissues than in tumor-adjacent normal tissues. We examined the expression of these miRs in 125 (cancer cases, 83; noncancer cases, 42) of 136 cytologic samples. Expression of all 4 miRs was significantly higher in patients with lung cancer than in those without lung cancer. Among samples judged as benign or indeterminate, levels of these miRs were also significantly higher in patients with lung cancer than in those without lung cancer. Conclusions: The analysis of miR expression in LBC samples might be helpful for primary lung cancer diagnosis.